Novel combinatorial therapy of oncolytic adenovirus AdV5/3-D24-ICOSL-CD40L with anti PD-1 exhibits enhanced anti-cancer efficacy through promotion of intratumoral T-cell infiltration and modulation of tumour microenvironment in mesothelioma mouse model - Garofalo, Mariangela; Wieczorek, Magdalena; Anders, Ines; Staniszewska, Monika; Lazniewski, Michal; Prygiel, Marta; Zasada, Aleksandra Anna; Szczepińska, Teresa; Plewczynski, Dariusz; Salmaso, Stefano; Caliceti, Paolo; Cerullo, Vincenzo; et al. (Frontiers in Oncology, 2023)
Malignant mesothelioma is a rare and aggressive cancer type. Despite improvements in cancer treatments, there are still no curative treatment modalities for advanced stage of the malignancy.In this study we evaluated the anti-tumor effectiveness of novel combinatorial therapy encasing AdV5/3-D24-ICOSL-CD40L, an oncolytic vector, with an anti PD-1 monoclonal antibody. The vector's efficacy was confirmed in vitro in three mesothelioma cell lines -H226, Mero-82 and MSTO-211H, and subsequently antineoplastic properties in combination with anti PD-1, was evaluated in xenograft H226 mesothelioma BALB/c and humanized NSG mouse models. Anticancer efficacy was attributed to reduced tumor volume and enhanced infiltration of tumor infiltrating lymphocytes, including activated cytotoxic T cells (GrB+CD8+). We additionally observed a correlation between tumor volume and activated CD8+ tumor infiltrating lymphocytes.Transcriptomic analysis carried out on resected human tumor tissue confirmed these findings and revealed upregulation of CD83 and CRTAM, as well as several chemokines (CXCL3, CXCL9, CXCL11) in tumor microenvironment. Furthermore, we observed that the combinatorial therapy had the strongest effect on lowering mesothelin and MUC16 levels. Gene set enrichment analysis suggests that the combinatorial therapy results in changes to the expression of genes belonging to the "adaptive immune response" gene ontology category. Combinatorial therapy involving oncolytic adenovirus with checkpoint inhibitors may improve anti-cancer effectiveness and survival by targeted cancer cell destruction and triggering of immunogenic cell death. Our results support further assessment of the AdV5/3-D24-ICOSL-CD40L in combination with checkpoint inhibitors as novel therapeutic perspectives for the treatment of mesothelioma.